Relations between Ethical Climate and Job Satisfaction: The Case of the Siauliai County State Tax Inspectorate - Toleikienė, Rita; Slaboševičiūtė, Kristina; Sapiegienė, Lina (Socialiniai tyrimai, 2014)
This article deals with the significance and importance of ethical climate in an organization. The typology of ethical climate is pointed out; the main aspects related to ethical climate are discussed, such as ethical behaviour, organizational commitment, and job satisfaction. Different Lithuanian and foreign scholars’ research papers and research carried out on the subject of ethical climate have been analysed and systematized. In applying theoretical knowledge and practical methodology, the research has been carried out on ethical climate in the Siauliai County State Tax Inspectorate. The research revealed the existing types of ethical climate in the organization, the external influential factors, and their relationship with the ethical climate on the employees’ job satisfaction in the organization. After summarizing the results of the research the following conclusions have been drawn up: the type of ethical climate of public interests is dominated in the Siauliai County State Tax Inspectorate, the office employees are concerned about the society welfare and try not to violate its interests. It has been concluded that the employees of the organization are most satisfied with their relationship with executives. The conclusions of scholars have been confirmed that caring, law and rules, independence, efficiency, public interest ethical climate types, and staff’s job satisfaction correlate and are related among themselves.